2018
DOI: 10.1002/mds.27314
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and CGG repeat‐related slowing of manual movement in fragile X carriers: A prodrome of fragile X‐associated tremor ataxia syndrome?

Abstract: Early-developing cerebellar or fronto-motor tract white matter changes, previously documented in MRI studies, may underlie motor slowing that occurs before clinically observable neurological symptoms associated with FXTAS. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Once there is significant white matter disease, the progression of further neurological dysfunction is thought to escalate, although the progression of FXTAS may be quite variable ( 33 ). A recent study by Shickman et al suggested that motor slowing may be measurable in asymptomatic premutation carriers before clinically observed motor or tremor symptoms arise in FXTAS ( 34 ). Future studies that examine white matter changes and subclinical motor signs of FXTAS may clarify which carriers are at greatest risk of developing clinical FXTAS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Once there is significant white matter disease, the progression of further neurological dysfunction is thought to escalate, although the progression of FXTAS may be quite variable ( 33 ). A recent study by Shickman et al suggested that motor slowing may be measurable in asymptomatic premutation carriers before clinically observed motor or tremor symptoms arise in FXTAS ( 34 ). Future studies that examine white matter changes and subclinical motor signs of FXTAS may clarify which carriers are at greatest risk of developing clinical FXTAS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While the results reported here are compelling, the study is not without limitations. Given the longitudinal aspect of this project, it is critically important that we continue to follow and track the progression of these biomarkers in conjunction with various neurological and neuropsychological symptoms, in particular motor control, balance and ataxia, and executive function (Shickman et al, 2018 ). Indeed, it will be critical to confirm whether or not the current group of non-converters remains asymptomatic, and if these findings remain in a larger cohort of Converters and Non-converters.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it appears that atrophy of the midbrain and pons cross-sectional area may be a common phenotypic characteristic for FMR1 premutation carriers, while reductions in MCP width may be prognostic to FXTAS symptoms and progression. While we endeavor to assess to clinical viability of MCP width as a biomarker of FXTAS through our ongoing research, we compel clinicians to monitor and assess changes in the MCP, primarily for atrophy in width and hyperintensities, as well as other FXTAS radiological signs in premutation carriers at risk for FXTAS or with subtle non-specific clinical changes e.g., (Shickman et al, 2018 ). In sum, MCP width in FMR1 premutation carriers may be a candidate biomarker to clinically identify patients in prodromal and early stages of FXTAS to help guide candidates for treatment and perhaps monitor response.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of subtle changes in the integrity of white matter in premutation male carriers without, or prior to, the occurrence of FXTAS [70][71][72], and of abnormal trajectories in cerebellar and brain stem volumes from early adulthood in these carriers [73] has provided direct evidence for preclinical brain changes. Indirect evidence for the pathological process relevant to neural involvement in non-FXTAS male carriers has also been obtained during the last decade [74,75], by observing the relationship between CGG expansion size and a modified combined measure of the three motor scales used individually in this study. However, there has been less evidence so far of neural involvement in non-FXTAS female carriers apart from a few reports of the presence of executive dysfunction [34], and early changes in postural stability [35].…”
Section: Discussionmentioning
confidence: 79%